Narrative skills in Russian-Greek Cypriot bilingual children - Karpava, Sviatlana; Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2019)
Narrative tasks tap into the cognitive, linguistic and social skills of the speaker/narrator. In this study the effect of bilingualism on macro-structural narrative abilities is investigated. Macrostructure deals with higher-order hierarchical organisation, episodic structure and story grammar components (Gagarina et al., 2016), reflecting a universally acquired ability (IlluzCohen and Walters, 2012). The aim of this study is to evaluate narrative skills of Russian– Cypriot Greek bilingual children in both of their languages. 22 simultaneous bilingual children participated in the study, 9 boys and 13 girls, born in Cyprus (father Greek-Cypriot and mother Russian). They ranged in chronological age from 6 to 14;6 years and attend primary/secondary school, where the language of instruction is Standard Modern Greek. The dominant society language is Cypriot Greek, while the home (weak/minority) language is Russian. The children had limited exposure to Russian, mostly at home only, and a low level of schooling in Russian, with only 1–2 hours of Russian lessons per week (Saturday school). The multilingual assessment instrument for narratives (LITMUS-MAIN; Gagarina et al., 2012, 2015) was used to assess narrative comprehension and production. Participants were also tested on a battery of cognitive-linguistic measures: the Cypriot adaptation of the Diagnostic Verbal IQ Test (Theodorou, 2013), the Russian Proficiency Test for Multilingual Children (Gagarina et al., 2010), a digit span test, a word span test, a fluency test, and Raven’s Coloured Progressive Matrices. The analysis of the narrative productions (see table 1) showed that, based on macro-structure measures (story structure, story complexity, internal state terms, comprehension), the bilingual children overall had higher scores in retelling than in telling mode and in Cypriot Greek than in Russian. Better performance in Russian was only found for story structure and story complexity (in telling mode). Also, the overall number of internal state terms in Russian narrative production was higher than in Cypriot Greek (in telling mode). Unsurprisingly, narrative abilities improve with age. Statistical analysis showed that age, schooling and cognitive abilities affect bilingual narrative skills. Overall, the results are in line with previous studies as narrative generation (telling) is considered to be more difficult than retelling due to prior presented script and scaffolding effects (Gagarina et al., 2016). Cypriot Greek is the majority language for these children, who are less experienced with the Russian language. This can explain their better performance in that language. Language dominance and use, the quantity and quality of input, frequency and consistency of exposure as well as the task effect should be taken into consideration when assessing linguistic and discourse abilities of bilingual children. Due to the increasing number of multilingual children in Cyprus, it is important to assess their linguistic and cognitive development and to distinguish early between typically developing and possibly languageimpaired children. The study of language acquisition norms for typical language development, language delay, and impairment can help prevent misdiagnosis of bilingual children.
Keywords: Narrative productions; Narrative abilities